2023
DOI: 10.1002/acn3.51744
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72 expansions are the most common cause of genetic frontotemporal dementia in a Southeast Asian cohort

Abstract: Objective Frontotemporal dementia (FTD) encompasses a spectrum of neurodegenerative disorders, including behavioural variant FTD (bvFTD), semantic variant primary progressive aphasia (svPPA) and non‐fluent variant PPA (nfvPPA). While a strong genetic component is implicated in FTD, genetic FTD in Asia is less frequently reported. We aimed to investigate the frequency of Southeast Asian FTD patients harbouring known genetic FTD variants. Methods A total of 60 FTD‐spectrum patients (25 familial and 35 sporadic) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
1
0
0
Order By: Relevance
“…4A, Table S17). In agreement with current known epidemiological studies, we observed that pathogenic alleles in 11,[37][38][39][40] . Given that the initial ancestry assignments for our cohort were based on genome-wide data, we performed local ancestry analysis to check for admixture in these individuals, confirming that the expanded repeat alleles segregated on haplotypes of African and South Asian ancestry (Methods).…”
Section: Red Mutation Frequency In Different Populationssupporting
confidence: 93%
“…4A, Table S17). In agreement with current known epidemiological studies, we observed that pathogenic alleles in 11,[37][38][39][40] . Given that the initial ancestry assignments for our cohort were based on genome-wide data, we performed local ancestry analysis to check for admixture in these individuals, confirming that the expanded repeat alleles segregated on haplotypes of African and South Asian ancestry (Methods).…”
Section: Red Mutation Frequency In Different Populationssupporting
confidence: 93%